(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2024)
The global prevalence of two-wheelers is experiencing a notable surge, particularly evident in developing countries, attributed to their economical price points and widespread accessibility. Their compact dimensions, manoeuvrability, and user-friendly nature have solidified their status as among the most prevalent forms of transportation worldwide. In the context of this study, we undertook a comprehensive examination of spinal injuries observed in post-mortem assessments of individuals involved in motorized two-wheeler accidents. Our findings underscore a significant trend: cervical spine injuries emerge as the most prevalent type of injury across both helmeted and non-helmeted riders. This analysis sheds light on the critical importance of understanding the specific injury patterns associated with two-wheeler accidents, serving as a foundational resource for informing public policy initiatives aimed at enhancing safety measures and mitigating the risks associated with this increasingly prevalent mode of transportation. By elucidating the prevalence and characteristics of spinal injuries in such incidents, this research contributes valuable insights towards fostering safer road environments and reducing the toll of two-wheeler accidents on individuals and communities worldwide. It is intended that the data provided by this study would serve to cover the information gap in this area and contribute to known facts, facilitating policy planning and guiding necessary measures.